Ecological risk assessment of the antibiotic enrofloxacin applied to Pangasius catfish farms in the Mekong Delta, Vietnam. (January 2015) - Andrieu, Margot; Rico, Andreu; Phu, Tran Minh; Huong, Do Thi Thanh; Phuong, Nguyen Thanh; Van den Brink, Paul J.
Highlights: We assessed the risks of enrofloxacin (ENR) and its main metabolite ciprofloxacin (CIP). Maximum ENR and CIP concentrations in aquaculture effluents were 0.68 and 0.25 μg L −1 . ENR and CIP accumulated in sediments down-stream the effluent discharge point. Tropical freshwater organisms showed high tolerance to ENR and CIP exposure. Only microbial communities are expected to be affected by ENR and CIP residues. Abstract: Antibiotics applied in aquaculture production may be released into the environment and contribute to the deterioration of surrounding aquatic ecosystems. In the present study, we assessed the ecological risks posed by the use of the antibiotic enrofloxacin (ENR), and its main metabolite ciprofloxacin (CIP), in a Pangasius catfish farm in the Mekong Delta region, Vietnam. Water and sediment samples were collected in a stream receiving effluents from a Pangasius catfish farm that had applied ENR. The toxicity of ENR and CIP was assessed on three tropical aquatic species: the green-algae Chlorella sp. (72 h – growth inhibition test), the micro-invertebrate Moina macrocopa (48 h – immobilization test), and the Nile tilapia ( Oreochromis niloticus ). The toxic effects on O. niloticus were evaluated by measuring the cholinesterase (ChE) and catalase (CAT) activities in the fish brain and muscles, respectively, and by considering feed exposure and water exposure separately. Ecological risks were assessed by comparing maximum exposure concentrations with predicted no effect concentrations for cyanobacteria, green algae, invertebrates and fish derived with available toxicity data. The results of this study showed that maximum antibiotic concentrations in Pangasius catfish farm effluents were 0.68 μg L −1 for ENR and 0.25 μg L −1 for CIP (dissolved water concentrations). Antibiotics accumulated in sediments down-stream the effluent discharge point at concentrations up to 2590 μg kg −1 d.w. and 592 μg kg −1 d.w. for ENR and CIP, respectively. The calculated EC50 values for ENR and CIP were 111 000 and 23 000 μg L −1 for Chlorella sp., and 69 000 and 71 000 μg L −1 for M. macrocopa, respectively. Significant effects on the ChE and CAT enzymatic activities of O. niloticus were observed at 5 g kg −1 feed and 400–50 000 μg L −1, for both antibiotics. The results of the ecological risk assessment performed in this study indicated only minor risks for cyanobacteria communities, suggesting that residual concentrations of ENR and CIP after medication are not likely to result in severe toxic effects on exposed aquatic ecosystems. However, more studies should be performed by considering other antibiotic treatments used in Pangasius catfish production and the potential ecotoxicological effects of relevant antibiotic mixtures on sediment communities.